Efeito da adição de psyllium (plantago ovata) na qualidade e na resposta glicêmica de pães sem glúten - Fratelli, Camilly [UNIFESP] (2016)
This study aims to simultaneously improve the technological, sensorial and nutritional quality of gluten-free bread (GFB) by the addition of psyllium to the formulation. A 22 full factorial design was used to investigate the main and interaction effects of psyllium - P (2.86 to 17.14% flour basis - fb) and water - W (82.14 to 117.86% fb) additions on GFB physical properties and acceptability. A total of 7 trials were carried out, comprising four for the factorial and three as central points. The fitted models (R2= 95.8-99.8%, p?0,02) showed that P and W interaction increases bread specific volume, crumb softness, and appearance, color, aroma, flavor, texture and overall acceptability scores of GFB. The model fitted for sensory acceptability scores were used to optimize GFB. Four promising formulations were defined: one from the multiple response desirability function (D= 0,99), named as formulation A prepared with 2.86% P and 82.14% W (fb) which received acceptability scores ? 8 on a 10-cm hybrid hedonic scale; and the other three, selected by the overlaid contour plot in order to achieve acceptable formulations (scores ? 7) enriched with the highest P levels, formulations B- 7.14% P e 91.10% A, C- 15.35% P e 117.86% A, and D- 17.14% P e 117.86% A (fb). The formulations C and D presented 7.8% and 9.2% of dietary fiber, respectively; which represents a three and four-fold increase of the fiber content compared to the control formulation. These formulations presented 3.9 and 4.6 g of P / 50g portion, physiologically relevant amounts of this dietary fiber with functional properties. A shelf-life study was performed for the formulations A - D, by the monitoring and evaluation the physical properties, microbiological safety and acceptability during 96h-storage, compared to the control GFB formulation and two formulations of wheat bread (WB1 and WB2). The results showed that among the GFB, the formulation D showed the lowest staling rate, and was the only one that maintains good acceptability for 72h-storage; with the same aroma, texture and flavor acceptability scores than WB1 and WB2. The glycemic response evaluation showed that the control GFB (0% P) had a high glycemic index (GI = 67) and glycemic load (GL = 14). The addition of 17.14% P (fb) in GFB formulation (formulation D) caused a significant reduction of the glycemic response, which resulted in a product with low GI (50) and low GL (9). Psyllium could be regarded as a technological and nutritional improver of GFB, which makes possible handling and molding the gluten-free dough, enhancing the structure, texture, appearance, acceptability and shelf-life of GFB, while increased the dietary fiber content and reduced the glycemic response of this food product, which can provide nutritional and functional benefits to patients with gluten related disorders.